Odpowiedzi

Najlepsza Odpowiedź!
2009-11-04T15:19:45+01:00
A) 3(2x-1)-5(x-3)+6(3x-4)=83
6x - 3 - 5x +15+18x-24=83
19x=96
x= 96/15

b) 4(x+4)-7(2x-1)+9(3x-4)=30
4x+16-14x+7+27x-36=10
17x=24
x=24/17

c) 8(7-4y)-7(4y+1)+5(8y-1)=39
56-32y-28y-7+40y-5=39
-20y=-4
y=4/20

d) 3(2x+1)-5(12x-7)+7(6x-1)=23
6x+1-60x+35+42x-7=23
-12x=-6
x=1/2

tyle tylko chciało mi się :D
2009-11-04T16:35:49+01:00
A)3(2x-1)-5(x-3)+6(3x-4)=83
6x-3-5x+15+18x-24=83
19x=83+3-15+24
19x=95/:19
x=5

b)4(x+4)-7(2x-1)+9(3x-4)=30
4x+16-14x+7+27x-36=30
17x=30-16-7+36
17x=43/:17
x=2,53

c) 8(7-4y)-7(4y+1)+5(8y-1)=39
56-32y-28y-7+40y-5=39
-20y=-5/:(-20)
y=0,25

d) 3(2x+1)-5(12x-7)+7(6x-1)=23
6x+3-60x+35+42x-7=23
-12x=23-3-35+7/:(-12)
x=0,666

e) 0,2x+0,5x+5(5x-1)-2,7x=6,5
0,2x+0,5x+25x-5-2,7x=6,5
23x=1,5/:23
x=0,065

f) 0,3(0,4x-1,2)+0,36x=0,6
0,12x-0,36+0,36x=0,6
0,48x=0,96/0,48
x=2